A Numerical Model for the Multiwavelength Lightcurves of PSR J0030+0451 - Chen, Alexander Y.; Yuan, Yajie; Vasilopoulos, Georgios (The Astrophysical Journal, 2020)
Recent modeling of Neutron Star Interior Composition Explorer (NICER) observations of the millisecond pulsar PSR J0030+0451 suggests that the magnetic field of the pulsar is non-dipolar. We construct a magnetic field configuration where foot points of the open field lines closely resemble the hotspot configuration from NICER observations. Using this magnetic field as input, we perform force-free simulations of the magnetosphere of PSR J0030+0451, showing the three-dimensional structure of its plasma-filled magnetosphere. Making simple and physically motivated assumptions about the emitting regions, we are able to construct the multiwavelength lightcurves that qualitatively agree with the corresponding observations. The agreement suggests that multipole magnetic structures are the key to modeling this type of pulsar, and can be used to constrain the magnetic inclination angle and the location of radio emission.
Keywords: 1062; 1408; 1822; 633; 998; Astrophysics - High Energy Astrophysical Phenomena; Gamma-ray sources; Magnetospheric radio emissions; Millisecond pulsars; Rotation powered pulsars; X-ray sources